2015
DOI: 10.1073/pnas.1512653112
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function in the brain links anxiety with social subordination

Abstract: Dominance hierarchies are integral aspects of social groups, yet whether personality traits may predispose individuals to a particular rank remains unclear. Here we show that trait anxiety directly influences social dominance in male outbred rats and identify an important mediating role for mitochondrial function in the nucleus accumbens. High-anxious animals that are prone to become subordinate during a social encounter with a low-anxious rat exhibit reduced mitochondrial complex I and II proteins and respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
274
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(298 citation statements)
references
References 61 publications
23
274
0
1
Order By: Relevance
“…In general, the scototaxic response of adult zebrafish to the light/dark box test in this study was consistent with the behavioural response previously observed for this paradigm [18]. In mammals, highly anxious individuals often display a subordinate status [26]. Therefore, assuming that trait anxiety also has an important consequence for social status in zebrafish, we would predict that adults derived from embryonic anoxia would have lower anxiety levels.…”
Section: Discussionsupporting
confidence: 90%
“…In general, the scototaxic response of adult zebrafish to the light/dark box test in this study was consistent with the behavioural response previously observed for this paradigm [18]. In mammals, highly anxious individuals often display a subordinate status [26]. Therefore, assuming that trait anxiety also has an important consequence for social status in zebrafish, we would predict that adults derived from embryonic anoxia would have lower anxiety levels.…”
Section: Discussionsupporting
confidence: 90%
“…ACCEPTED MANUSCRIPT 26 Concerning behavioural outcomes in the EPM and OF, we showed an increase of closed arms entries in the EPM and an increase of line crossing in the OF in male and female offspring.…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…Further insights for a key role of mitochondrial function in specific brain regions in influencing complex social behaviors have been provided by a series of studies in rats relating anxiety with diminished social competitiveness (Hollis et al, 2015; van der Kooij et al, 2017), a phenomenon that has also been highlighted in humans (Goette et al, 2015). In rats, lower mitochondrial function in the nucleus accumbens was observed in high-anxious animals compared to their less anxious littermates, and was causally implicated in their low social competitiveness (Hollis et al, 2015).…”
Section: Mitochondrial Function In the Brain Influences Social Bementioning
confidence: 99%
“…In rats, lower mitochondrial function in the nucleus accumbens was observed in high-anxious animals compared to their less anxious littermates, and was causally implicated in their low social competitiveness (Hollis et al, 2015). More specifically, high-anxious animals that are prone to become subordinate during a social encounter exhibited reduced mitochondrial respiratory capacity, decreased ATP levels, and increased ROS production in the nucleus accumbens.…”
Section: Mitochondrial Function In the Brain Influences Social Bementioning
confidence: 99%
See 1 more Smart Citation